Fault-Related Controls on Upward Hydrothermal Flow: An Integrated Geological Study of the Têt Fault System, Eastern Pyrénées (France) - Audrey Taillefer; Roger Soliva; Laurent Guillou-Frottier; Elisabeth Le Goff; Guillaume Martin; Michel Seranne (Geofluids)
The way faults control upward fluid flow in nonmagmatic hydrothermal systems in extensional context is still unclear. In the Eastern Pyrénées, an alignment of twenty-nine hot springs (29°C to 73°C), along the normal Têt fault, offers the opportunity to study this process. Using an integrated multiscale geological approach including mapping, remote sensing, and macro- and microscopic analyses of fault zones, we show that emergence is always located in crystalline rocks at gneiss-metasediments contacts, mostly in the Têt fault footwall. The hot springs distribution is related to high topographic reliefs, which are associated with fault throw and segmentation. In more detail, emergence localizes either (1) in brittle fault damage zones at the intersection between the Têt fault and subsidiary faults or (2) in ductile faults where dissolution cavities are observed along foliations, allowing juxtaposition of metasediments. Using these observations and 2D simple numerical simulation, we propose a hydrogeological model of upward hydrothermal flow. Meteoric fluids, infiltrated at high elevation in the fault footwall relief, get warmer at depth because of the geothermal gradient. Topography-related hydraulic gradient and buoyancy forces cause hot fluid rise along permeability anisotropies associated with lithological juxtapositions, fracture, and fault zone compositions.